The Impacts of Using Business Information Systems on Operational Effectiveness in Hungary - Peter Sasvari (International Journal of Emerging Research in Management &Technology, 2013)
Business expectations regarding the introduction of business information systems were investigated according to company size categories. The results clearly showed that according to the majority of the respondents the information supply for decision-makers improved. In contrast, business information systems as a means of improving competitiveness were only regarded by corporations, this aspect was only around the average in the other company size categories. The respondents evaluated to what extent the usage of business information system provided assistance for their economic analyses. The obtained results show that business information systems can be utilized well in controlling and reporting. There are differences in their judgement by size categories. Particularly corporations can take advantage of the support of business information systems mainly in the field of planning, plan-actual analysis and the exploration of cost reducing possibilities.
Keywords: C10; M15; 330; Business Information Systems; Hungary; micro-; small and medium-sized enterprises